MODEL PEMILIHAN TINGKAT TEKNOLOGI, SUMBER PEMBIAYAAN DAN KELEMBAGAAN USAHA DALAM PENGEMBANGAN AGROINDUSTRI BERBASIS NAGARI DENGAN PROSES JEJARING ANALITIK - Nofialdi, Irawadi Jamaran, Syafrida Manuwoto, Marimin, Yandra Arkeman dan Sapta Raharja (E-jurnal Agro-Industri Indonesia, 2012)
ABSTRACT The objective of this research was to determine a technology level, financial and institutional resources in agroindustrial development based on nagariconcept in West Sumatra. This model was built using Analytical Network Process (ANP). The selection result of technology level shows the priority of technology level requirement. The fulfilled requirements for the selection are the efforts to transform the current technologies to a more appropriate technology (teknologi tepatguna). The result shows, that effective financial supports are in form of co-operative and governmental sources. The chosen agroindustrial institution is in form of cooperative and the collaboration between cooperative the and investors. Keywords: a technology level, financial and institutional resources, analytical network process, agroindustry of nagari